1988
DOI: 10.3109/10826088809058855
|View full text |Cite
|
Sign up to set email alerts
|

Interactional Variables Associated with Retention and Success in Residential Drug Treatment

Abstract: The present study was designed to identify variables associated with client retention and success at the Rocco Antenucci Memorial Adult Residential Drug Treatment Center in Akron, Ohio. Multiple stepwise regressions were utilized to evaluate the variance contributed by demographic, psychological, and interactional variables associated with client retention for 100 program participants. Degree of social support and employment at discharge accounted for 63% of the variance. Factors related to successful treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(26 citation statements)
references
References 21 publications
3
23
0
Order By: Relevance
“…Client characteristics include age (Deck & Carlson, 2005;Friedmann et al, 2001;Hser et al, 2004), poly substance use (Hiltunen & Eklund, 2002;Sorensen et al, 1985), treatment motivation (Joe et al, 1999;Longshore & Teruya, 2006), and client's psychological function (Grella & Wugalter, 1997;Joe et al, 1999). Social characteristics include family support (Dobkin et al, 2002;Siddal & Conway, 1988), community support (Brown et al, 2004), and peer support (Booth et al, 2004). Some studies found that interactions between these factors were also significant in predicting treatment success (Ball and Ross, 1991;Chou, Hser, & Anglin, 1998;Hser et al, 2001).…”
Section: Introductionmentioning
confidence: 95%
“…Client characteristics include age (Deck & Carlson, 2005;Friedmann et al, 2001;Hser et al, 2004), poly substance use (Hiltunen & Eklund, 2002;Sorensen et al, 1985), treatment motivation (Joe et al, 1999;Longshore & Teruya, 2006), and client's psychological function (Grella & Wugalter, 1997;Joe et al, 1999). Social characteristics include family support (Dobkin et al, 2002;Siddal & Conway, 1988), community support (Brown et al, 2004), and peer support (Booth et al, 2004). Some studies found that interactions between these factors were also significant in predicting treatment success (Ball and Ross, 1991;Chou, Hser, & Anglin, 1998;Hser et al, 2001).…”
Section: Introductionmentioning
confidence: 95%
“…This observation may be of particular importance for individuals with substance-use disorders and cognitive impairment. Clients in treatment for substance-use disorders are known to be positively infl uenced by abstinence-supporting social infl uences (Knight and Simpson, 1996;Manuel et al, 2007;Richter et al, 1991;Siddall and Conway, 1988;Zywiak et al, 2002) and negatively infl uenced by maintaining relationships with drinking-supporting individuals (e.g., see, Marlatt, 1985;McCrady, 2004); and the infl uence of agents in the social environment can become amplifi ed in treatment clients with diminished cognitive capacity. This amplifi ed infl uence would then represent an alternative change process operating outside the context of treatment but serving to promote or impede sustained behavioral changes needed for recovery.…”
mentioning
confidence: 99%
“…For AUD clients in general, treatment retention (Siddall and Conway, 1988) and recovery (Knight and Simpson, 1996;Richter et al, 1991) are facilitated by abstinence-supporting social influences, whereas risk for relapse is enhanced by negative social influences (e.g., see Marlatt, 1985;McCrady, 2004). Empirical studies that use a variable-centered approach to studying social support networks have identified abstinence role models, larger social networks, and the number of supportive relationships as most predictive of positive outcomes (Zywiak et al, 2002).…”
mentioning
confidence: 99%